Aromatase Inhibitor-Associated Musculoskeletal Syndrome: Understanding Mechanisms and Management - Hyder, Tara; Marino, Christopher C.; Ahmad, Sasha; Nasrazadani, Azadeh; Brufsky, Adam M. (Frontiers in Endocrinology, 2021)
Aromatase inhibitors (AIs) are a key component in the chemoprevention and treatment of hormone receptor-positive (HR+) breast cancer. While the addition of AI therapy has improved cancer-related outcomes in the management of HR+ breast cancer, AIs are associated with musculoskeletal adverse effects known as the aromatase inhibitor-associated musculoskeletal syndrome (AIMSS) that limit its tolerability and use. AIMSS is mainly comprised of AI-associated bone loss and arthralgias that affect up to half of women on AI therapy and detrimentally impact patient quality of life and treatment adherence. The pathophysiology of AIMSS is not fully understood though has been proposed to be related to estrogen deprivation within the musculoskeletal and nervous systems. This review aims to characterize the prevalence, risk factors, and clinical features of AIMSS, and explore the syndrome’s underlying mechanisms and management strategies.